Bibliometrical analysis of hydrogen storage. (25th October 2019) - He, Ming; Zhang, Yu; Gong, Linghui; Zhou, Yuan; Song, Xiufang; Zhu, Weiping; Zhang, Meimei; Zhang, Zhao
Abstract: On the basis of literature research and expert consultation on hydrogen storage, this paper is the first to use the bibliometric method to conduct data mining and visualization analysis for the development of international hydrogen storage research. A total of 22612 publications on hydrogen storage published from 1900 to 2019 were obtained. The number of citations and research authors per year is also counted. Some indicators are used in this paper to evaluate countries, research institutions, researchers, journals and so on, such as IF, H-index, TC and CPA. We also use VOS viewer to visualize keywords. Results show that the literature on hydrogen storage has been recently increasing, particularly from 2009 to 2018. The study on hydrogen storage has entered a stable and high-frequency period, with a total of 16348 papers, which account for 72.3% of the total research papers on hydrogen storage. During this period, the number of authors who studied hydrogen storage exceeded 3000 and reached 3265 in 2008. The average number of citations per year was 2672.41. China's total volume of publications reached 7239, with 12 research institutions ranking among the top 20, and 9 researchers ranking among the top 10 in this field. China plays an important role in international research on hydrogen storage. However, the US accounts for the highest h-index (220), the highest TC (233734) and the highest CPA (59.86), which shows that the United States has the strongest influence on the research of hydrogen storage. In terms of the number of articles, the INTERNATIONAL JOURNAL OF HYDROGEN ENERGY ranked first with 3413 articles, followed by the JOURNAL OF ALLOYS AND COMPOUNDS with a total of 2131 articles. Notably, the average number of citations of the articles in the FORUM OF THE AMERICAN CHEMICAL SOCIETY and the ANGEWANDTE CHEMIE-INTERNATIONAL EDITION exceeded 150 times, that is, 165.2 and 157.14 with impact factors of 14.695 and 12.257, respectively. International hydrogen storage disciplines, such as chemistry (71.38%), materials science (38.81%), and energy science (22.10%), are distributed or related interdisciplinary research areas. The research hotspots of hydrogen storage are chemical and adsorption hydrogen storages, such as hydrogen fuel cells, metal hydride, metal–organic framework, and carbon nanotube. By contrast, research on high-pressure gaseous and liquid hydrogen storages is relatively few. Researchers are suggested to give more attention to high-pressure gaseous and liquid hydrogen storages and consider the entire process of hydrogen energy utilization. Moreover, they are suggested to propose the optimal hydrogen storage mode by combining various hydrogen storage methods. Researchers must not only increase the number of their published papers but also enhance the quality. Cooperation between countries and research institutions should be further strengthened, and exchange between different disciplines is also needed to promote the interdisciplinary development of hydrogen storage and transportation. Highlights: Hydrogen storage is quantitatively analyzed using bibliometrics. The characteristics of hydrogen storage research in countries, institutions, researchers and journals are analyzed. The high frequency keywords were statistically analyzed, and the cluster and correlation degree were analyzed. Cooperation between countries and institutions were visualized. The hotspots of hydrogen storage research are analyzed and some suggestions are put forward.